Fractional Order Nonlinear Control of Heat System - Jesus, Isabel S. (2019)
In the last decade, the interest in the area of fractional calculus and its applications has increased significantly. In this paper, we study a heat diffusion system in a fractional calculus perspective. A fractional order nonlinear controller is proposed, and its tuning, in the viewpoint of several performance indices, is analyzed. The simulations demonstrate the good performance of the proposed fractional-order structure.